STRATEGI PENINGKATAN KAPASITAS DALAM RANGKA PENINGKATAN PRODUKTIFITAS IKM DI KELURAHAN PARIT RANTANG - Nova Yarsina; Rahmad Rahmad (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Abstract: This study aims to reveal: To find out what factors can affect the increase in the capacity of SMEs in Parit Rantang Village, Payakumbuh City and to. Knowing the IKM Strategy in Parit Rantang Village, Payakumbuh City in increasing capacity in order to increase IKM productivity This research consists of 3 stages of interviews. Informants in the first stage of the interview are the actors of IKM totaling 6 people, to obtain information on the factors that influence the capacity building of IKM. In the second stage of the interview, the informants are 5 experts, to see the level of importance and effectiveness of the government's response to the factors and the third stage of the interview is the stakeholders of the Payakumbuh city government to get input on the right strategy in increasing the factors that affect the capacity building of SMEs . The analytical tool used is the Delphi method. Result of this study are: . Factors to increase the capacity of SMEs are Capital, Quality of Human Resources, Business Facilities and Infrastructure, Marketing, Quality of Production, Financial / Bookkeeping management, Technology, Promotion, Availability of Raw Materials and Environmental Support, results based on the level of importance Factors that greatly affect the capacity of SMEs are The quality of human resources with a score of 5.00 or 100% with the criteria Very important and the results based on the Effectiveness Level of the government's response to the factors it is known that Capital has a high government response effectiveness with a score of 4.20 or 84% with the Effective criteria, while the level of effectiveness of the government response is low. Low is Financial Management / Bookkeeping with a score of 2.80 or 56% with Less Effective Criteria, the strategy from the research results is Improved financial management / bookkeeping by providing bookkeeping training and collaborating with academics / campuses, Technology Improvement by providing trainers and facilities IT technology and appropriate technology and Increasing the availability of raw materials by increasing supervision from the government on the availability of raw materials and stability of raw material pricesKeywords: Strategic Management, Productivity, Capacity, Delphi Method.